Higher Serum Uric Acid Level Predicts Non-alcoholic Fatty Liver Disease: A 4-Year Prospective Cohort Study - Wei, Fengjiang; Li, Jiaxin; Chen, Chen; Zhang, Kai; Cao, Li; Wang, Ximo; Ma, Jun; Feng, Shuzhi; Li, Wei-Dong (Frontiers in Endocrinology, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) has become a serious diseases affecting people's health in the world. This paper studies the causal relationship between NAFLD and serum uric acid (SUA) levels. Methods: During the 4 years of follow-up in a fixed cohort that was established in 2014, 2832 follow-up people without NAFLD were finally included in this study. The study population was divided into four groups according to baseline SUA levels. Cox hazard regression model and Kaplan-Meier survival curves analysis were used to predict risk factors of NAFLD. The receiver operating characteristic (ROC) curve analyses were used to determine SUA cutoffs for predicting NAFLD. Results: The cumulative prevalence rates of NAFLD was 33.97% (962/2832), 38.93% (758/1947) in males, and 23.05(204/885) in females. The results showed that males had a higher incidence of NAFLD(=68.412, P=0.000). The cox regression analysis disclosed that the hazard ratios (HRs) of NAFLD [95% CI] were 1.431(95%CI: 1.123~1.823), 1.610(95%CI:1.262~2.054) and 1.666(95%CI: 1.287~2.157) across the second to the fourth quartile of SUA adjusted for other confounders. The SUA cutoffs, sensitivity, specificity, and area under the curve (AUC) (95%CI) were ≥288.5μmol/L, 75.5%, 46.5%, 0.637(0.616~0.658), respectively, for total; ≥319.5μmol/L, 65.8%, 48.4%, 0.590(0.564~0.615), respectively, for males; and ≥287.5μmol/L, 51.0%, 75.6%, 0.662(0.619~0.704), respectively, for females. Kaplan-Meier survival curves revealed that individuals with higher SUA level had an increased risk of NAFLD in comparison to lower SUA level (P=0.000). Conclusion: SUA is positively correlated with NAFLD, and elevated SUA level can be used as an independent predictor for NAFLD.